A meta-analysis review on the antimicrobial activity of Blumea balsamifera (L.) DC., Cassia plata (L.), and Peperomia pellucid (L.) Kunth - Monserate, Lorraine Kaye G.; Maglangit, Fleurdeliz (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Antimicrobial resistance potentiates the burden imposed by bacterial and fungal infections that lead to serious illnesses and food security threat. This paper provides meta-analyses of the antimicrobial susceptibility of Blumea balsamifera, Cassia alata, and Peperomia pellucida. The study collates the specific bioactive compounds isolated from the plants and compares the antimicrobial effects of the plant parts. The meta-analyses were carried out in odds ratios to determine whether the over-all effect favourably results in a low (≤ 1000 μg/mL) or high minimum inhibitory concentration (MIC) (> 1000 μg/mL) using Review Manager version 5.4.1. Results showed that the studies had no preference in low or high MIC of the three plants against Gram-positive bacteria (GP), Gram-negative bacteria (GN), and fungi. Kruskal-Wallis test was performed in RStudio to compare the MIC of the three plants and the MIC of the various plant parts. There was no significant difference on the actions of the three plants against the GP and GN (X2 = 1.82, p = .40)(X2 = 0.27, p = 0.87), but the activities of B. balsamifera and C. alata vary against fungi (X2 = 21.84, p < 0.05) rendering B. balsamifera as a more potent antifungal. The roots of B. balsamifera exhibited the lowest MIC against GP (X2 = 10.99, p = .01) and GN (X2 = 15.58, p = 0.001). C. alata seeds had the lowest MIC against the bacterial groups (X2 = 11.96, p = 0.02) (X2 = 29.24, p < 0.001) while the stem was more potent against fungi (X2 = 4.73, p = 0.19). The aerial parts of P. pellucida were the most active in inhibiting GN (X2 = 31.07, p < 0.001) while the stem was the most effective against GP (X2 = 11.96, p = 0.02). There were 22 bioactive compounds from identified from the three plants possessing a highly active antimicrobial effect. The results of the study offer future prospects on gathering pieces of evidence on the use of the three plants to combat diseases caused by bacteria and fungi.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022